Person-centred care for dementia patients (back-end and front-end development) - Leow, Mandfred Hong Jie (Nanyang Technological University, 2024)
This report documents the development and transition of the Person-Centred Care System (PEAR) from a monolithic .NET 5-based application to a microservices architecture with ReactJS for the front end. The need for this migration arose from .NET 5's end of support, leading to critical security risks and limitations in scalability. The new microservices architecture aims to improve modularity, fault tolerance, and deployment efficiency. It enables independent development and scaling of backend services, making the system more maintainable and adaptable to future needs.